Micronization of Three Active Pharmaceutical Ingredients Using the Rapid Expansion of Supercritical Solution Technology. Issue 6 (9th February 2020) - Fang, Chun-Hao; Chen, Pei-Hua; Chen, Yan-Ping; Tang, Muoi
Abstract: The rapid expansion of supercritical solution (RESS) technology was applied to recrystallize and micronize three active pharmaceutical ingredients (APIs) of monobenzone, ethylparaben, and kojic acid. All unprocessed (original) APIs had a large mean particle size over 200 μm with wide particle size distribution. Supercritical carbon dioxide served as the solvent to extract each API in a high‐pressure vessel. The nearly saturated supercritical solution was then expanded through a capillary spray nozzle to ambient pressure state. The APIs were recrystallized in a very short time period. The final API particles with submicron sizes were obtained with much less intensity of crystallinity. The optimal RESS process parameters and the improved result of the in vitro dissolution test for the API of ethylparaben are reported. Abstract : Three active pharmaceutical ingredients of monobenzone, ethylparaben, and kojic acid were recrystallized and micronized employing the rapid expansion of supercritical solution (RESS) technology. The mean particle sizes of these ingredients were micronized down to submicron level. Enhanced dissolution behavior was observed for the RESS‐processed active pharmaceutical substances.